2008
DOI: 10.1529/biophysj.107.114983
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Amyloid β-Peptides on the Lysis Tension of Lipid Bilayer Vesicles Containing Oxysterols

Abstract: Amyloid beta-peptides (Abeta) applied directly from solution to model lipid membranes produced dramatic changes in the material properties of the bilayer when certain oxysterols were present in the bilayer. These effects were dependent on both lipid and peptide composition, and occurred at peptide concentrations as low as 100 nM. Using micropipette manipulation of giant unilamellar vesicles, we directly measured the lysis tension of lipid bilayers of various compositions. The glycerophospholipid 1-stearoyl-2-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 67 publications
3
25
0
Order By: Relevance
“…Those observations could be explained in different ways. The incorporated protein may increase the lysis tension of the membrane 43 , which would reduce the breaking of the membrane. It could also affect the viscosity of the membrane and prevent the reformation of the membrane after the osmotic shock.…”
Section: Discussionmentioning
confidence: 99%
“…Those observations could be explained in different ways. The incorporated protein may increase the lysis tension of the membrane 43 , which would reduce the breaking of the membrane. It could also affect the viscosity of the membrane and prevent the reformation of the membrane after the osmotic shock.…”
Section: Discussionmentioning
confidence: 99%
“…Studies performed on supported phospholipid membranes revealed that exposure to Aβ modifies morphology and local mechanical properties of bilayers, reducing the force required to break through the membrane with an AFM probe (Dante et al, 2011). The lysis tension of unilamellar vesicles containing oxysterols are altered by exposure to nanomolar concentration of Aβ peptides (Kim and Frangos, 2008). Collectively, these results suggest Aβ can negatively impact the mechanical integrity of lipid membranes.…”
Section: The Interaction Of Aβ With Lipid Surfacesmentioning
confidence: 99%
“…7keto is the major product of cholesterol oxidation induced by reactive oxygen species [22] and is shown to significantly affect membrane properties and interaction with Ab [23][24][25]. We employed a heterogeneous cell-sized liposome system, composed of cholesterol, equal concentrations of unsaturated phospholipid and saturated phospholipid.…”
Section: Introductionmentioning
confidence: 99%